BETWEEN CARE AND DEPRIVATION OF LIBERTY: WHAT FUTURE DIRECTIONS AND REGULATIONS FOR RESTRAINT? - GOURIOT, Mylène; GRANDAZZI, Guillaume; MOUTEL, Grégoire (MEDECINE LEGALE DROIT MEDICAL, 2025)
Despite very restrictive legislative provisions on the use of restraint by healthcare professionals, it is a measure that is often used in health and medico-social establishments, which raises questions about the ethics of care and support practices. We need to think about how to regulate the deprivation of liberty measures used in institutions, in a context where restraint is seen primarily as a form of care and is essentially a medical responsibility.